An anion exchange composite membrane, a preparation method and application thereof
Patent Information
- Application Number
- CN202411304895.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-12
- Filing Date
- 2024-09-19
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-09-19
AI Technical Summary
然而AEM在电解工况条件下的实际耐久性远差于离位环境测定的稳定性
[0074]与未添加高热导无机材料的AEM(如含有阳离子基团的聚合物)技术相比,本发明的优点如下:
Smart Images

Figure CN118943440B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ion exchange membrane technology, and more specifically, relates to a durable organic / inorganic composite anion exchange membrane, its preparation method and application, which are mainly used in water electrolysis, fuel cells, flow batteries and CO2 electrolysis. Background Technology
[0002] Hydrogen energy is a crucial component of the future energy system, driving the transition from fossil fuels and reducing carbon emissions in the energy sector. High-efficiency, low-cost, and zero-emission renewable energy-based water electrolysis for hydrogen production is a key technology for hydrogen energy utilization. Anion exchange membrane electrolyzers (AEMWE) integrate the advantages of alkaline electrolyzers (AWE) and proton exchange membrane electrolyzers (PEMWE), offering advantages such as high current density, high energy efficiency, fast response speed, and adaptability to flexible loads. In particular, AEMWE uses inexpensive transition metal catalysts instead of the precious metal catalysts found in PEMWE, significantly reducing electrolyzer costs; and it uses pure water or low-concentration alkaline aqueous solutions as the electrolyte, avoiding the corrosion of equipment caused by the strongly alkaline solutions of AWE. Therefore, AEMWE is a highly cost-effective and performance-advantageous water electrolysis hydrogen production technology.
[0003] Anion exchange membranes (AEMs) are the core components of AEMWEs, typically composed of a polymer backbone, cation exchange groups, and hydroxide ions, to achieve OH- ion exchange. - AEMs play a crucial role in gas transfer and isolation, significantly impacting the efficiency and durability of hydrogen production through water electrolysis. However, AEMs primarily face challenges related to OH... - It suffers from generally low ionic conductivity and insufficient stability under high temperature and strong alkaline conditions.
[0004] Currently, research on AEMs mainly focuses on designing polymer backbones, side chains, and cation exchange groups based on original chemical design, optimizing ion channel size, structure, and structural orientation, and regulating membrane component structure and ion transport channels to improve the ionic conductivity and thermal alkali stability of AEMs. However, the actual durability of AEMs under electrolysis conditions is far worse than the stability measured in situ. For example, quaternary ammonium salt polymers achieve 1200 hours of situ stability, while the durability of electrolyzers based on these polymers is less than 72 hours, which severely limits the commercialization of AEM-based electrochemical devices. Therefore, achieving excellent in-situ durability under electrolyzer conditions is a significant challenge in AEM development. Summary of the Invention
[0005] 1. The problem to be solved
[0006] Numerous existing documents demonstrate a significant difference between AEM (Aqueous Electrolytic Emulator) operating conditions and off-site stability. However, no existing technology has revealed the fundamental reason for this difference. In this invention, the inventors, through in-situ temperature measurement experiments, discovered that the AEM temperature is higher under electrolytic cell operating conditions. Analysis revealed that the AEM's thermal conductivity is the lowest among all components of the electrolytic cell. During electrolysis, the Joule heat generated by the current accumulates within the AEM, leading to deterioration of mechanical properties, decreased ionic conductivity, and device failure. This issue is the primary reason for the significant difference between AEM operating conditions and off-site stability.
[0007] Based on the above findings, and addressing the issue of poor durability of AEM electrolyzers in existing technologies, this invention aims to improve the thermal conductivity of AEM by reducing the thermal conductivity difference between AEM and other components in the electrolyzer. This invention provides an anion exchange composite membrane that effectively dissipates heat, lowers the membrane temperature, and improves its durability. This is significant for enhancing the thermal-alkali stability of anion exchange membranes and provides a new approach for the future development of highly durable anion exchange membranes.
[0008] 2. Technical Solution
[0009] This invention proposes a strategy for developing high thermal conductivity anion exchange composite membranes to improve the thermal conductivity of anion exchange membranes. Experimental results show that adding thermally conductive materials can effectively improve the in-situ durability of AEM (Anion Exchange Membrane). Specifically, this invention provides the following technical solutions:
[0010] [Anion Exchange Composite Membrane]
[0011] The first aspect of the present invention provides an anion exchange composite membrane, the composite membrane comprising component A and component B;
[0012] Component A is a polymer material containing cationic groups, and the polymer material is selected from one or more of the following: chitosan, polyarylpiperidine, polyvinyl alcohol, polyphenylene ether, polyetherketone, polyphenylene sulfide, polybenzimidazole, polyarylene pyridine, polyarylene-alkylene, polystyrene, perfluorosulfonic acid resin, poly(styrene) oxide, polyethylene, and poly(ethylene-tetrafluoroethylene) polymer materials;
[0013] Component B is an inorganic material;
[0014] The thermal conductivity of component B is not less than 5 times that of component A;
[0015] The thermal conductivity of the anion exchange composite membrane is not less than 1.5 W / m. –1 K –1 .
[0016] Preferably, component A and component B are physically mixed and bonded by non-covalent bonds.
[0017] As described herein, the methods for testing thermal conductivity are well known in the art. The theoretical thermal conductivity of general materials can be obtained from literature records or by testing using the following methods:
[0018] The thermal conductivity of the composite membrane can be obtained by laser pulse method, 3ω test method, photothermal reflection method, scanning thermal microscopy, etc.
[0019] As described herein, "polymer materials" refers to high molecular weight materials (typically up to 10) composed of repeatedly linked bonds. 4 ~10 6 ) compounds.
[0020] As described herein, "polymer material containing cationic groups" refers to the modification of the main chain or branches of a specified polymer with cationic functional groups.
[0021] This invention improves the thermal conductivity of anion exchange composite membranes by adding inorganic materials with high thermal conductivity to polymer materials containing cationic groups, thereby enhancing the durability of the anion exchange composite membrane in the electrolyzer.
[0022] As a preferred embodiment of any of the first aspects of the present invention, the thermal conductivity of the anion exchange composite membrane is not less than 2 W / m². –1 K –1 Further preferably, it should be no less than 5W m –1 K –1 Not less than 10W m –1 K –1 The increased thermal conductivity of the anion exchange composite membrane helps to reduce the thermal conductivity difference between the AEM and other components in the electrolyzer, thereby reducing heat accumulation in the AEM; it also improves the thermal stability of the composite membrane.
[0023] As a preferred embodiment of any of the first aspects of the present invention, the theoretical thermal conductivity of the inorganic material is not less than 5 W / m². –1 K –1 Further preferably, it is not less than 10W m –1 K –1 Not less than 20W m –1 K –1 Not less than 50W m –1 K –1 Not less than 100W m –1 K –1 Not less than 200W m –1 K –1 Not less than 300W m –1 K –1 Not less than 400W m–1 K –1 .
[0024] As a preferred embodiment of any of the first aspects of the present invention, the thermal conductivity of component B is not less than 8 times that of component A, more preferably not less than 10 times that of component A, not less than 20 times that of component A, not less than 50 times that of component A, not less than 100 times that of component A, and not less than 200 times that of component A.
[0025] It is worth noting that, from the perspective of improving the thermal conductivity of the anion exchange composite membrane, component B inorganic material with higher thermal conductivity is preferred.
[0026] As stated herein, "inorganic materials" refers to materials made from inorganic substances alone or in combination with other substances. Generally, it refers to materials prepared from raw materials such as silicates, aluminates, borates, phosphates, germanates, etc., and / or oxides, nitrides, carbides, borides, sulfides, silicides, halides, etc., through specific processes.
[0027] As a preferred embodiment of any aspect of the present invention, the inorganic material is selected from one or more of boron nitride, silicon carbide, molybdenum disulfide, zirconium dioxide, silicon dioxide, magnesium oxide, carbon nanotubes, graphene, silicon nitride, and aluminum oxide. Boron nitride and carbon nanotubes are preferred.
[0028] Among them, the theoretical in-plane thermal conductivity of boron nitride is approximately 600 W / m. –1 K –1 The out-of-plane theoretical thermal conductivity is approximately 30 W / m². –1 K –1 The theoretical thermal conductivity of carbon nanotubes is approximately 6000 W / m. –1 K –1 The theoretical thermal conductivity of silicon carbide is approximately 490 W / m². –1 K –1 The theoretical thermal conductivity of molybdenum disulfide is approximately 40 W / m². –1 K –1 The theoretical thermal conductivity of zirconium dioxide is approximately 6.2 W / m². –1 K –1 The theoretical thermal conductivity of silicon dioxide is approximately 0.8–1.3 W / m². –1 K –1 The theoretical thermal conductivity of magnesium oxide is approximately 36 W / m². –1 K –1 The theoretical thermal conductivity of graphene is approximately 5000 W / m. –1 K –1The theoretical thermal conductivity of silicon nitride is approximately 100 W / m. –1 K –1 The theoretical thermal conductivity of alumina is approximately 150 W / m. –1 K –1 .
[0029] This invention introduces inorganic materials with intrinsically high thermal conductivity, such as boron nitride and carbon nanotubes, into a polymer film with rapid ion conduction to construct a 3D continuous thermally conductive network in an AEM, thereby forming an AEM with rapid thermal conduction channels and improving the in-situ durability of the AEM.
[0030] As a preferred embodiment of any of the first aspects of the present invention, the inorganic material is preferably layered boron nitride, and the confined space formed by the layered boron nitride helps to achieve rapid ion transport, thereby improving the conductivity of the anion exchange membrane.
[0031] As a preferred embodiment of any aspect of the first aspect of the present invention, the cationic group is selected from one or more cationic groups containing N, S, quaternary phosphonium, or metal complexes. The N-containing cationic group is selected from one or more of acyclic quaternary ammonium ions, heterocyclic quaternary ammonium ions, guanidinium, and imidazolium salts. The quaternary ammonium cation can be trimethyl quaternary ammonium salt, benzenetrimethyl quaternary ammonium salt, bicyclic aliphatic spiruline quaternary ammonium salt, 1-methylmethylazonium quaternary ammonium salt, 1-methylpyrrolidoneonium quaternary ammonium salt, quinoneonium quaternary ammonium salt, 1-methylpiperidineonium quaternary ammonium salt, 1,4-dimethylpiperidineonium quaternary ammonium salt, 1,3,5-trimethylpiperidineonium quaternary ammonium salt, and 1,2,6-trimethylpiperidineonium quaternary ammonium salt, etc.
[0032] As described herein, "quaternary ammonium cation" refers to the modification of the main chain or side chain of a specified polymer with quaternary ammonium functional groups.
[0033] As a preferred embodiment of any of the first aspects of the present invention, the mass percentage of inorganic materials in the anion exchange composite membrane, based on the total mass of the anion exchange composite membrane, is selected from any of the following numerical ranges:
[0034] 1–50%, 2–50%, 3–50%, 4–50%, 5–50%, 10–50%, 15–50%, 20–50%, 25–50%, 30–50%, 35–50%, 40–50%, 45–50%;
[0035] 1–45%, 2–45%, 3–45%, 4–45%, 5–45%, 10–45%, 15–45%, 20–45%, 25–45%, 30–45%, 35–45%, 40–45%;
[0036] 1–40%, 2–40%, 3–40%, 4–40%, 5–40%, 10–40%, 15–40%, 20–40%, 25–40%, 30–40%, 35–40%;
[0037] 1–35%, 2–35%, 3–35%, 4–35%, 5–35%, 10–35%, 15–35%, 20–35%, 25–35%, 30–35%;
[0038] 1–30%, 2–30%, 3–30%, 4–30%, 5–30%, 10–30%, 15–30%, 20–30%, 25–30%;
[0039] 1–25%, 2–25%, 3–25%, 4–25%, 5–25%, 10–25%, 15–25%, 20–25%;
[0040] 1–20%, 2–20%, 3–20%, 4–20%, 5–20%, 10–20%, 15–20%;
[0041] 1–15%, 2–15%, 3–15%, 4–15%, 5–15%, 10–15%;
[0042] 1-10%, 2-10%, 3-10%, 4-10%, 5-10%;
[0043] 1-5%, 2-5%, 3-5%, 4-5%.
[0044] Preferably, based on the total mass of the anion exchange composite membrane, the inorganic material content in the anion exchange composite membrane is 5% to 30% by mass, excluding 30%; more preferably 5% to 29%; and more preferably 5% to 25%. This invention improves the thermal conductivity of the anion exchange membrane (AEM) by adding highly thermally conductive inorganic materials to polymer materials containing cationic groups, particularly quaternized polymer materials, thereby reducing the thermal conductivity difference between the AEM and other components in the electrolytic cell, reducing heat accumulation, and further improving the in-situ durability of the AEM under electrolytic conditions. The higher the amount of highly thermally conductive inorganic material added, the higher the thermal conductivity of the AEM; however, excessive addition of inorganic materials can alter the mechanical properties of the AEM. Furthermore, experiments show that the electrical conductivity of the AEM is not positively correlated with the amount of highly thermally conductive inorganic material added; when the amount of highly thermally conductive inorganic material added reaches a certain value, the electrical conductivity of the anion exchange composite membrane decreases. Therefore, considering the mechanical properties and electrical conductivity of the AEM, the amount of highly thermally conductive inorganic material added should be kept within a reasonable range.
[0045] As a preferred embodiment of any of the first aspects of the present invention, the thickness of the anion exchange composite membrane is 5 to 500 μm, preferably 20 to 100 μm, and more preferably 30 to 50 μm.
[0046] [Preparation method of anion exchange composite membrane]
[0047] The second aspect of the present invention provides a method for preparing an anion exchange composite membrane according to any embodiment of the first aspect of the present invention, comprising:
[0048] Step 1: Preparation of casting solution: Mix polymer material A containing cationic groups and inorganic material B in a solvent;
[0049] Step 2: Forming a film from the casting solution.
[0050] As a preferred embodiment of any of the second aspects of the present invention, the preparation method specifically includes:
[0051] Step 1: Prepare the casting solution;
[0052] Polymer material A containing cationic groups is dissolved in a solvent to obtain a polymer dispersion, while inorganic material B is uniformly dispersed in the same solvent to obtain an inorganic material dispersion. The two dispersions are then mixed uniformly to obtain a casting solution of A / B mixture; or
[0053] Polymer material A and inorganic material B are directly dissolved or dispersed in the same solvent to obtain a casting solution of A / B mixture;
[0054] Step 2: Formation of film from casting solution:
[0055] Using the casting solution obtained in step one, a membrane is formed by different casting methods, namely casting, blade coating and coating, to form an anion exchange composite membrane.
[0056] As a preferred embodiment of any of the second aspects of the present invention, in step two, the volume percentage of the polymer dispersion is 99% to 1%, and the volume percentage of the inorganic material dispersion is 1% to 99%.
[0057] As a preferred embodiment of any of the second aspects of the present invention, the polymer material is chitosan.
[0058] As a preferred embodiment of any of the second aspects of the present invention, the polymer material is a polyarylepiperidine polymer, such as poly(N-methylpiperidine-co-p-terphenyl).
[0059] As a preferred embodiment of any of the second aspects of the present invention, the inorganic material is boron nitride. Preferably, it is layered boron nitride.
[0060] As a preferred embodiment of any of the second aspects of the present invention, the inorganic material is carbon nanotubes.
[0061] As a preferred embodiment of any of the second aspects of the present invention, in step one, the concentration of A in the casting solution is 0.3 g / mL to 1.0 g / mL.
[0062] As a preferred embodiment of any of the second aspects of the present invention, in step two, a film is formed from the casting liquid using a casting method, a scraping method, or a coating method.
[0063] As a preferred embodiment of any of the second aspects of the present invention, in step two, the ambient pressure at which the film is evaporated from the casting solution during film formation is 100 Pa to 10 Pa. 5 Pa.
[0064] As a preferred embodiment of any of the second aspects of the present invention, in step two, the temperature for evaporation to form a film is room temperature to 150°C.
[0065] [Membrane Electrode Assembly]
[0066] A third aspect of the present invention provides a membrane electrode assembly, the membrane electrode assembly comprising an anion exchange composite membrane according to any embodiment of the first aspect of the present invention, or an anion exchange composite membrane prepared according to any embodiment of the second aspect of the present invention; and a catalyst coated on both sides of the anion exchange composite membrane, the catalyst comprising a cathode catalyst and an anode catalyst.
[0067] As a preferred embodiment of any third aspect of the present invention, the cathode catalyst is selected from one or more of Pt / C, NiFe, NiFeV, and NiFeCo hydroxides.
[0068] As a preferred embodiment of any third aspect of the present invention, the anode catalyst is one or more of IrO2, RuO2, NiFe, NiFeV, and NiFeCo hydroxide.
[0069] Electrolytic cell
[0070] The fourth aspect of the present invention provides an electrolytic cell, the electrolytic cell comprising an anion exchange composite membrane according to any embodiment of the first aspect of the present invention, or comprising an anion exchange composite membrane obtained by the preparation method according to any embodiment of the second aspect of the present invention, or comprising a membrane electrode assembly according to any embodiment of the third aspect of the present invention.
[0071] Applications of Anion Exchange Composite Membranes
[0072] The fifth aspect of the present invention provides the application of an anion exchange composite membrane according to any embodiment of the first aspect of the present invention, or an anion exchange composite membrane obtained by the preparation method according to any embodiment of the second aspect of the present invention, or a membrane electrode assembly according to any embodiment of the third aspect of the present invention in water electrolysis, fuel cells, flow batteries, supercapacitors, or CO2 electrolysis.
[0073] 3. Beneficial effects
[0074] Compared with AEM technology that does not incorporate highly thermally conductive inorganic materials (such as polymers containing cationic groups), the advantages of this invention are as follows:
[0075] (1) This invention is the first to discover a crucial factor leading to the significant difference between the in-situ stability and the operating condition of the AEM (Anion Exchange Membrane). Specifically, among all components of the electrolyzer, the thermal conductivity of the AEM is the lowest. During electrolysis, the Joule heat generated by the current accumulates within the AEM, leading to deterioration of mechanical properties, decreased ionic conductivity, and device failure. Consequently, the electrolyzers using AEMs in the prior art have poor durability. To address this issue, this invention provides an anion exchange composite membrane. This composite membrane incorporates a high thermal conductivity inorganic material into a polymer material containing cationic groups, resulting in an anion exchange composite membrane with high thermal conductivity. Experimental results show that the addition of the high thermal conductivity inorganic material significantly improves the in-situ durability of the anion exchange composite membrane.
[0076] (2) Furthermore, experiments in this invention show that inorganic materials can construct a 3D thermally conductive network in anion exchange composite membranes, forming a structure with a fast thermal conduction channel. The confined space formed helps the rapid transport of ions, thereby improving the conductivity of the anion exchange membrane.
[0077] (3) The present invention further demonstrates that when the amount of high thermal conductivity inorganic material, especially layered boron nitride, added to the anion exchange composite membrane is within a specific range, the electrical conductivity and thermal conductivity of the anion exchange composite membrane can be guaranteed at the same time, so that the anion exchange composite membrane can maintain high in-situ durability.
[0078] (4) The preparation method of the anion exchange composite membrane of the present invention only requires physical mixing of a polymer containing cationic groups with a high thermal conductivity inorganic material to form a casting solution, and then preparing the membrane. The preparation process is simple, the material selection range is wide, and the conditions are simple.
[0079] (5) Due to its high thermal and electrical conductivity, the anion exchange composite membrane of the present invention can inhibit the degradation reaction of the polymer base membrane and effectively extend the service life of the anion exchange membrane. It has good application prospects in a variety of energy storage and conversion devices, such as water electrolysis for hydrogen production, fuel cells, flow batteries, CO2 electrolysis and other fields. Attached Figure Description
[0080] Figure 1 This is a schematic diagram of the structure of the inorganic material-doped high thermal conductivity anion exchange composite membrane of the present invention;
[0081] Figure 2 SEM cross-sectional images of the QCS / BN (left) prepared in Example 1 and the QAPPT / BN (BN volume ratio 8.9%) composite membrane (right) prepared in Example 6;
[0082] Figure 3 The graph shows the test data of electrical conductivity and thermal conductivity of the QCS / BN composite films prepared in the examples and comparative examples;
[0083] Figure 4 The graph shows the tensile strength data of the QCS / BN composite films prepared in the examples and comparative examples;
[0084] Figure 5 The graph shows the actual internal temperature data (left) and water electrolysis stability test data (right) of the QCS / BN composite membranes prepared in the examples and comparative examples during operation;
[0085] Figure 6 The graph shows the long-term stability test data of the QCS / BN composite membrane prepared in the examples and comparative examples for water electrolysis.
[0086] Figure 7 The graph shows the conductivity and tensile strength data of the QAPPT / BN composite films prepared in the examples and comparative examples;
[0087] Figure 8 The graph shows the thermal conductivity (left) and long-term stability test data of the QAPPT / BN composite membranes prepared in the examples and comparative examples (right). Detailed Implementation
[0088] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the term “and / or” as used herein includes any and all combinations of one or more of the associated listed items.
[0089] The chitosan used in this example was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0090] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0091] As used herein, the term “about” is used to provide for the flexibility and imprecision associated with a given term, measure, or value. Those skilled in the art can readily determine the degree of flexibility for a particular variable.
[0092] Concentration, amount, and other numerical data may be presented in range format herein. It should be understood that such range format is used solely for convenience and brevity and should be flexibly interpreted to include not only the values explicitly stated as the limits of the range, but also all individual values or subranges encompassed within the range, as if each value and subrange were explicitly stated. For example, a range of values from about 1 to about 4.5 should be interpreted to include not only the explicitly stated limits of 1 to 4.5, but also individual numbers (such as 2, 3, 4) and subranges (such as 1 to 3, 2 to 4, etc.). The same principle applies to ranges that describe only a single value, such as “less than about 4.5,” which should be interpreted to include all the aforementioned values and ranges. Furthermore, this interpretation should apply regardless of the breadth of the range or characteristic described.
[0093] like Figure 1 The diagram shown is a schematic representation of the high thermal conductivity ion exchange composite electrolytic cell doped with inorganic materials according to the present invention. The AEM electrolytic cell is mainly composed of an anion exchange membrane, a catalyst layer, a gas diffusion layer, and bipolar plates in a sealed assembly. Working principle: It involves two half-reactions: oxygen evolution reaction and hydrogen evolution reaction. Using pure water or an alkaline solution as the electrolyte, and driven by a voltage of 1.8–2.5V, the electrolytic device electrochemically decomposes water to produce oxygen and hydrogen. The core technology of the AEM electrolytic cell is the anion exchange membrane, which absorbs OH-... - It transports gases from the cathode to the anode while preventing cross-contamination of gases across the membrane.
[0094] In the examples and comparative examples, the thermal conductivity was obtained by directly measuring the film using a laser thermal conductivity analyzer (LFA467 Superflash) under a nitrogen atmosphere.
[0095] The present invention will be further described below with reference to specific embodiments.
[0096] Example 1
[0097] This embodiment uses chitosan as a polymer to provide a method for preparing a high thermal conductivity anion exchange membrane by constructing a 3D thermally conductive network, specifically including the following steps:
[0098] Step 1: Preparation of casting solution;
[0099] (1) Preparation of quaternized chitosan polymer:
[0100] Chitosan is prepared by a ring-opening reaction with a quaternizing agent under alkaline conditions, specifically including the following:
[0101] Weigh 4g of chitosan (viscosity > 400 mPa·s) and dissolve it in 1% acetic acid solution. Stir mechanically at 1500 rpm for 2 hours at 25°C. Slowly add NaOH solution; a white flocculent precipitate will appear in the solution. Wash 2-3 times with deionized water to obtain a gel-like substance.
[0102] Take another 12g of the quaternizing reagent 2,3-epoxypropyltrimethylammonium chloride and dissolve it in a certain amount of a mixed solution of water and isopropanol.
[0103] The obtained chitosan gel was placed in a round-bottom flask, and an appropriate amount of water and isopropanol solution was added. The mixture was mechanically stirred at 1000 rpm at 80°C. The prepared 2,3-epoxypropyltrimethylammonium chloride solution was added to the round-bottom flask in several portions. The reaction was carried out for 8 hours, cooled, and the product was washed 2-3 times with ethanol. After drying, the quaternized chitosan polymer was obtained for later use.
[0104] (2) Preparation of casting solution:
[0105] The quaternized chitosan polymer (QCS, 2.0 g) prepared in step (1) was dissolved in a 1% acetic acid solution. After complete dissolution, layered boron nitride nanosheets were doped with the quaternized chitosan polymer at a volume percentage of 10.6% (BN accounts for 25% of the mass percentage of the anion exchange composite membrane, and the mass of the anion exchange composite membrane is based on the total mass of the quaternized chitosan polymer and BN). The liquid was mixed evenly to obtain the QCS / BN casting solution.
[0106] Step 2: Preparation of a high thermal conductivity anion exchange membrane;
[0107] The casting solution of QCS / BN prepared in step one was poured into a plastic petri dish and placed under an ambient pressure of 10. 5 The membrane was evaporated and cast at room temperature to 150°C under Pa conditions. The resulting membrane was then peeled off and immersed in NaOH solution for ion exchange to obtain the QCS / BN thermally conductive anion exchange composite membrane. The thickness of the anion exchange composite membrane is approximately 30–50 μm, and its thermal conductivity is approximately 6.2 W / m². –1 K –1 .
[0108] Example 2
[0109] The steps in this embodiment are basically the same as those in Example 1, except that: in step (2), the volume percentage of layered boron nitride nanosheets relative to the quaternized chitosan polymer is 1.8% (BN accounts for 5% of the mass percentage of the anion exchange composite membrane).
[0110] The resulting anion exchange composite membrane has a thickness of approximately 30–50 μm and a thermal conductivity of approximately 2.9 W / m². –1K –1 .
[0111] Example 3
[0112] The steps in this embodiment are basically the same as those in Example 1, except that in step (2), the volume percentage of layered boron nitride nanosheets relative to the quaternized chitosan polymer is 5.9% (BN accounts for 15% of the mass percentage of the anion exchange composite membrane).
[0113] The resulting anion exchange composite membrane has a thickness of approximately 30–50 μm and a thermal conductivity of approximately 4.0 W / m². –1 K –1 .
[0114] Example 4
[0115] The steps in this embodiment are basically the same as those in Example 1, except that: in step (2), the volume percentage of layered boron nitride nanosheets relative to the quaternized chitosan polymer is 16.1% (BN accounts for 35% of the mass percentage of the anion exchange composite membrane).
[0116] The resulting anion exchange composite membrane has a thickness of approximately 30–50 μm and a thermal conductivity of approximately 13.2 W / m². –1 K –1 .
[0117] Comparative Example 1
[0118] The steps of this comparative example are basically the same as those of Example 1, except that layered boron nitride nanosheets are not added in step (2).
[0119] A QCS anion exchange membrane with a thickness of approximately 30–50 μm was obtained, and its thermal conductivity was measured to be approximately 1.3 W / m² under the same conditions as in Examples 1–4. –1 K –1 .
[0120] Example 5
[0121] This embodiment is a test example of the anion exchange membranes obtained in Examples 1 to 4 and Comparative Example 1.
[0122] (I) SEM
[0123] The composite films with different boron nitride nanosheet doping ratios from Examples 1-4 and Comparative Example 1 were dried, and SEM cross-sectional images of the composite films were measured. The SEM image of the composite film prepared in Example 3 is shown below. Figure 2 As shown on the left, sheet-like boron nitride nanosheets were successfully dispersed in a polymer matrix to construct a 3D continuous thermally conductive network.
[0124] (II) Electrochemical Performance Testing
[0125] Thermal conductivity and electrochemical performance were tested on composite films with different doping ratios of layered boron nitride nanosheets in Examples 1, 3, and 4 and Comparative Example 1.
[0126] The thermal conductivity of the composite membrane was obtained by directly measuring the membrane under nitrogen atmosphere using a laser thermal conductivity analyzer (LFA467 Super Flash).
[0127] In OH - Before conductivity measurement, the composite membrane was immersed in 1M NaOH for 24 hours and washed with deionized water. The in-plane OH content of the composite membrane was measured using a four-electrode method at water temperatures ranging from 25°C to 90°C. – Conductivity. Electrochemical impedance spectroscopy (EIS) was performed at an electrochemical station (frequency from 100 kHz to 1 Hz). σ hydroxide conductivity was calculated using the following formula:
[0128]
[0129] Where L is the distance between the two electrodes in cm, R is the resistance obtained by EIS testing (the actual axial value at the high-frequency intercept) in Ω, and S is the cross-sectional area of the membrane in cm². 2 .
[0130] like Figure 3 As shown, the thermal conductivity of the composite film gradually increases from 0% to 15% BN doping volume percentage (relative to the polymer material containing cationic groups), but the electrical conductivity of the composite film reaches its highest value in the range of 5% to 10% BN doping volume percentage. Therefore, the preferred BN doping volume percentage in the QCS / BN anion exchange composite film is 5% to 10%.
[0131] (III) Mechanical Performance Testing
[0132] At a stretching speed of 6mm min -1 Tensile strength tests were performed on an ETNALN YTN~D5~PC tensile testing machine, and the average value was obtained from at least three tests. The sample size was 1.5cm*0.5cm.
[0133] The results show that in Examples 1-4 and Comparative Example 1, the tensile strength of the composite film significantly improved with increasing boron nitride nanosheet doping ratio, reaching its highest value when the volume ratio was between 5% and 10% (e.g., ...). Figure 4 (As shown), however, as the doping ratio of boron nitride nanosheets continues to increase, the tensile strength of the composite film decreases.
[0134] (iv) Conduct electrolytic water stability tests on the composite membrane.
[0135] Activation: The composite anion exchange membranes prepared in Examples 1, 2 and 4 and Comparative Example 1 were activated in 1M potassium hydroxide solution for at least 12 hours, then washed with deionized water until the pH value of the membrane surface was about 7, and dried for later use.
[0136] Prepare anode catalyst slurry and cathode catalyst slurry separately:
[0137] Preparation of anode catalyst slurry: Commercial IrO2 (RuO2 or non-precious metal catalysts can also be used) was used as the electrode catalyst for the electrocatalytic oxygen evolution reaction (OER). Anode catalyst (IrO2) and ion-conducting ionomer (FAA-3) at a mass ratio of 5:1 were added to isopropanol solvent, and then ultrasonically treated in an ice-water bath for 30-40 min to obtain the anode electrode ink, i.e., the anode catalyst slurry.
[0138] Preparation of cathode catalyst slurry: Commercial Pt / C (or non-precious metal catalysts) was used as the electrode catalyst for the electrocatalytic hydrogen evolution reaction (HER). A 5:1 mass ratio of cathode catalyst (Pt / C) and ion-conducting ionomer (FAA-3) was added to isopropanol solvent, and then ultrasonically treated in an ice-water bath for 30-40 min to obtain the cathode electrode ink, i.e., the cathode catalyst slurry.
[0139] The anolyte catalyst slurry and cathode catalyst slurry are directly sprayed onto both sides of the membrane, resulting in a membrane electrode assembly (MEA) with a thickness of approximately 60–80 μm. An effective square area of 4 cm² is fabricated. 2 MEA.
[0140] Before the experiment, the prepared MEA was soaked in 1M KOH aqueous solution for 12 hours.
[0141] The performance of a single cell was evaluated under controlled temperature on a water electrolysis apparatus, with 3 MkOH electrolyte in both electrodes and a flow rate of 10 mL / min. –1 , in 1A cm -2 The durability of the composite membrane was studied under constant current mode at a current density of 60℃.
[0142] During operation, the temperature of the electrolytic cell is monitored.
[0143] like Figure 5 As shown, with the increase of the volume ratio of thermally conductive boron nitride nanosheets, the in-situ temperature of the composite membrane during actual operation of the electrolytic cell can be effectively reduced; the voltage stability of water electrolysis is significantly improved.
[0144] like Figure 6 As shown, in long-term stability tests, the composite film with added boron nitride nanosheets exhibits significantly improved stability compared to the polymer film.
[0145] Example 6
[0146] This embodiment uses polyarylpiperidine as the polymer and provides a method for preparing a high thermal conductivity anion exchange membrane by constructing a 3D thermally conductive network, specifically including the following steps:
[0147] (I) Preparation of quaternized poly(N-methyl-piperidine-co-p-terphenyl) (QAPPT):
[0148] 1.69 g of p-terphenyl was dissolved in 8 mL of dichloromethane solution in a 25 mL three-necked round-bottom flask equipped with a mechanical stirrer. Then, 1.26 g of N-methyl-4-piperidinone was added and mixed thoroughly. At 0 °C, 0.72 mL of trifluoroacetic acid and 6 mL of trifluoromethanesulfonic acid were slowly added, and the mixture was stirred until it became viscous. The solution was then precipitated in 75 mL of ice-cold CH3OH. Large pieces of material were sheared to terminate the localized reaction, and the mixture was washed with deionized water until neutral. After drying at 60 °C for 24 hours, the N-methyl-piperidin-co-p-terphenyl polymer was obtained.
[0149] 1 g of the above polymer was dissolved in 20 mL of DMSO, and 0.89 g of K2CO3 was added. Then, 0.92 g of CH3I was added to the reaction system under light-protected conditions. The mixture was kept at 40 °C for 48 h. Afterward, the K2CO3 was removed by centrifugation, and the precipitate was collected in ethyl acetate. The precipitate was washed repeatedly with ethyl acetate and dried at 70 °C to obtain the product, quaternized poly(N-methyl-piperidine-co-p-terphenyl).
[0150] (II) Preparation of QAPPT / BN casting solution: The steps are the same as those in step (2) of Example 1, except that the quaternized chitosan is replaced with the quaternized poly(N-methyl-piperidine-co-p-terphenyl) obtained in this example. The doping mass ratio of boron nitride nanosheets to anion exchange composite membrane can be (0.05-0.25):1 (mass ratio). In this example, QAPPT / BN casting solutions with boron nitride nanosheets doping volume ratios of 4.4%, 8.9%, 13.5% and 18% to quaternized poly(N-methyl-piperidine-co-p-terphenyl) were prepared. These are converted to the percentage of BN doping mass relative to anion exchange composite membrane, which are 5%, 10%, 15% and 20%, respectively.
[0151] (III) Preparation of QAPPT / BN composite membrane:
[0152] The steps are the same as step two of Example 1: preparation of a high thermal conductivity anion exchange membrane, except that QCS / BN is replaced with QAPPT / BN with different volume ratios, and the thickness is approximately 30–50 μm. The thermal conductivity of QAPPT / BN with a doping volume ratio of 8.9% is 11.9 W / m². –1 K –1 .
[0153] Comparative Example 2
[0154] The steps in this comparative example are basically the same as those in Example 6, except that boron nitride nanosheets are not added.
[0155] A QAPPT anion exchange membrane was obtained with a thickness of approximately 30–50 μm and a thermal conductivity of approximately 0.95 W / m². –1 K –1 .
[0156] Example 7
[0157] This example is a test case of the anion exchange membrane prepared in Example 6 and Comparative Example 2, and the test conditions are the same as in Example 5.
[0158] like Figure 2 As shown on the right, boron nitride nanosheets were successfully dispersed in the polymer matrix.
[0159] like Figure 7 As shown, the conductivity test results of the polyarylpiperidine composite membrane indicate that the higher the doping ratio of boron nitride nanosheets, the higher the conductivity of the anion exchange composite membrane, reaching the highest value in the range of approximately 10%-15% (volume ratio). This suggests that constructing a 3D thermally conductive network in the anion exchange composite membrane with boron nitride (BN) can form a structure with rapid thermal conduction channels. The confined space formed facilitates the rapid transport of ions, thereby improving the conductivity of the anion exchange membrane.
[0160] Meanwhile, the tensile strength of the anion exchange composite membrane also reaches its highest value in the range of approximately 10%-15% (volume ratio).
[0161] like Figure 8 As shown, compared with the QAPPT anion exchange membrane without BN, the QAPPT / BN composite membrane (volume ratio 8.9% BN) has significantly improved thermal conductivity and voltage stability (400h) for water electrolysis.
[0162] According to the principles of this invention, the addition of thermally conductive materials can effectively improve the thermal conductivity of the polymer membrane and significantly enhance the stability of the composite membrane in water electrolysis applications. When the amount of thermally conductive material added is within a certain range, it can effectively improve the mechanical strength of the polymer membrane. Furthermore, within the confined space formed by the thermally conductive material, it can effectively improve the electrical conductivity of the polymer membrane. Therefore, in addition to the examples shown in the above embodiments, other thermally conductive materials can be used for doping, such as inorganic thermally conductive materials like silicon carbide, molybdenum disulfide, zirconium dioxide, silicon dioxide, magnesium oxide, graphene, silicon nitride, and alumina, all of which can improve the thermal conductivity and electrolytic stability of the ion exchange membrane to a certain extent.
[0163] The above description provides an illustrative overview of the present invention and its embodiments. This description is not restrictive, and the embodiments shown are merely one example of the invention's implementation. Actual implementations are not limited to these examples. Therefore, if those skilled in the art are inspired by this description and design similar implementations and examples without departing from the spirit of the invention, such designs should fall within the scope of protection of the present invention.
Claims
1. An anion exchange composite membrane, characterized in that, The composite membrane comprises component A and component B; Component A is a polymer material containing cationic groups, wherein the polymer material is selected from one or more of the following: chitosan, polyarylpiperidine, polyvinyl alcohol, polyphenylene ether, polyetherketone, polyphenylene sulfide, polybenzimidazole, polyarylene pyridine, polyarylene-alkylene, polystyrene, perfluorosulfonic acid resin, poly(styrene) oxide, and poly(ethylene-cotetrafluoroethylene) polymer materials; Component B is an inorganic material; the thermal conductivity of component B is not less than 5 times that of component A; the inorganic material is selected from one or more of boron nitride, silicon carbide, carbon nanotubes, graphene, silicon nitride, and aluminum oxide; Based on the total mass of the anion exchange composite membrane, the inorganic material content in the anion exchange composite membrane is 20%~45% by mass; The thermal conductivity of the anion exchange composite membrane is not less than 5 W / m. –1 K –1 .
2. The anion exchange composite membrane according to claim 1, characterized in that, The thermal conductivity of the anion exchange composite membrane is not less than 10 W / m. –1 K –1 .
3. The anion exchange composite membrane according to claim 2, characterized in that, The cationic group is selected from one or more cationic groups containing N, S, quaternary phosphorus, or metal complexes.
4. The anion exchange composite membrane according to claim 1 or 2, characterized in that, The thickness of the anion exchange composite membrane is 5~500μm.
5. The method for preparing the anion exchange composite membrane according to any one of claims 1 to 4, characterized in that, include: Step 1: Preparation of casting solution: Mix component A and component B in a solvent; Step 2: Forming a film from the casting solution.
6. A membrane electrode assembly, the membrane electrode assembly comprising the anion exchange composite membrane according to any one of claims 1 to 4; and a catalyst coated on both sides of the anion exchange composite membrane.
7. An electrolytic cell, the electrolytic cell comprising the anion exchange composite membrane according to any one of claims 1 to 4, or comprising the membrane electrode assembly according to claim 6.
8. The application of the anion exchange composite membrane according to any one of claims 1 to 4 or the membrane electrode assembly according to claim 6 in water electrolysis, fuel cells, flow batteries, supercapacitors or CO2 electrolysis.
Citation Information
Patent Citations
Anion exchange composite membrane as well as preparation method and application thereof
CN113621170A
Multifunctional radical scavenger, polymer electrolyte membrane including same, catalyst layer, membrane electrode assembly, and fuel cell
CN118302887A
Indigenous diaphragm and non-noble bi-functional catalysts based alkaline wastewaters electrolyzer
IN202441052211A
KR20230082246A